Extracapsular dissection versus superficial parotidectomy in pleomorphic adenoma: a decade-long experience from a tertiary care center in Bangladesh - Debnath, Timir Kumar; Biswas, Ashim Kumar; Barua, Raju; Hazari, Aslam; Samad, M. Abdus (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Pleomorphic adenoma is recognized as the most common benign tumor of the salivary glands, while malignant tumors like mucoepidermoid carcinoma, though less frequent, present complex management challenges. This study aims to evaluate the efficacy and safety of surgical techniques, specifically extracapsular dissection (ECD) and superficial parotidectomy (SP), in Bangladesh, where data on this topic is limited. Methods: Conducted over ten years (2014-2024) at the national center for hearing and speech for children and green life medical college and hospital, this retrospective cohort study analyzed records of 50 patients with histopathologically confirmed pleomorphic adenoma. Data included demographics, tumor characteristics, and surgical outcomes, with statistical significance set at p<0.05. Results: The cohort had a median age of 38 years, predominantly female (58%). The median tumor size was 4 cm, with most surgeries on the right side (52%). Preoperative diagnoses indicated 79.07% pleomorphic adenomas, with FNAC confirming 84.44% benign lesions. ECD was associated with larger tumors (mean size: 7.82 cm vs. 5.65 cm, p=0.0459) and a higher malignancy rate. Facial nerve preservation rates were 73.33% for ECD and 80.65% for SP. However, ECD had a higher complication rate, including temporary facial nerve paralysis (57.14% vs. 15.38%) and seroma formation (14.29% vs. 0%, p=0.021). Conclusions: This study underscores that pleomorphic adenoma is the predominant parotid gland pathology in Bangladesh. Both ECD and SP are effective surgical options, but careful planning and patient selection are crucial to minimize complications and enhance outcomes.